The development of molecular tools for the expression of prodrug converting enzymes in Clostridium sporogenes - Pennington, Oliver John (2006)
Despite intensive research, cancer remains one of the major causes of worldwide morbidity. It is widely believed, however, that if currently available anti-cancer drugs could be delivered specifically to tumours then the disease would have been mastered. The delivery of prodrug converting enzymes by clostridial spores specifically to the anoxic centres of tumours is one potential delivery mechanism. This is due to the extreme selectivity of spores to germinate solely in the hypoxic regions of tumours. Once germinated, the expression of a prodrug converting enzyme converts a systemical1y administered prodrug to a highly toxic drug only in the tumour. Previous studies using Clostridium acetobutylicum and Clostridium beijerinckii as the delivery vehicle highlighted that prodrug converting enzyme expression is only found in tumours. However, no significant anti-tumour affect was observed. Two possible reasons were evolved. Firstly, expression of the prodrug converting enzyme may be low, and/or, secondly, the tumours may not be colonised sufficiently to promote an antitumour effect.